Piezoelectric properties of Bi₂TeO₅ single crystals - Antonenko, A.M.; Domoratsky, K.V.; Kudzin, A.Yu.; Sadovskaya, L.Ya. (Condensed Matter Physics, 1999)
This paper is devoted to the measurement results of piezoelectric, dielectric and elastic tensor components in the temperature range between 20 °C and 400 °C. It was revealed that excitation resonance and antiresonance signals were possible without preliminary sample polarizing. Besides, the sound velocities measured along the main axes by echo-pulse method at room temperature are presented. У роботi наведенi результати вимiрювань компонент п’єзоелектричних, дiелектричних та пружних тензорiв у діапазонi температур 20–
400 °C. Виявлено, що збудження сигналiв резонансу та антирезонансу можливе без попередньої поляризацiї зразка. Луна-iмпульсним
методом отримано значення швидкостi звуку вздовж головних кристалографiчних осей при кiмнатнiй температурi.